2006
DOI: 10.1111/j.1368-5031.2006.00902.x
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary referral of patients from community care to cardiology lack diagnostic and clinical detail

Abstract: The quantity of referrals to secondary care is increasing. That the quality of medical referrals is decreasing is a common allegation yet has rarely been assessed. We report a time-limited, cross-sectional survey evaluating cardiological referral information quality. Referral letters (n = 218, excluding direct access pro formas) from GPs to the Cardiology Department at City Hospital, Birmingham, were collated and analysed over 2 months. A subset (n = 49) of these patients completed questionnaires assessing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…It is therefore possible that the effect of the intervention on patient experience could have been higher if the level of dissatisfaction with the healthcare cooperation had been higher in the local population. However, this also may suggest that although the hospital consultants often feel information is lacking in the referrals,38 39 this is not necessarily experienced as a problem by patients.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore possible that the effect of the intervention on patient experience could have been higher if the level of dissatisfaction with the healthcare cooperation had been higher in the local population. However, this also may suggest that although the hospital consultants often feel information is lacking in the referrals,38 39 this is not necessarily experienced as a problem by patients.…”
Section: Discussionmentioning
confidence: 99%
“…10 The absence of previous investigation results was noted in more than 50% of the referral letters in three separate studies, 3,22,24 patients' medical history was not routinely included in referral information, 13,16,25 and allergies 16,23 and clinical findings 5,17,18,22 were generally poorly recorded. These omissions may be due in part to the fact that there is no real consensus amongst different specialties on the ideal information to be included in a referral letter, beyond an agreement on broad information categories.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we undertook a detailed literature review of studies analysing the content of GP referral letters. Twenty-four studies were identified, covering a wide range of specialties [1][2][3][4][5][6][7] and different referral systems. [8][9][10] Several evaluated the impact of guidelines [11][12][13][14] or use of structured referral forms 15,16 on referral information.…”
Section: Introductionmentioning
confidence: 99%
“…To assure high quality further down in the treatment process, the referral letter from the GP should contain all the necessary information in a context of shared understanding among the GP, the patient, and hospital staff [27]. However, a number of publications have pointed to the varying quality and content of referrals in clinical practice [28–30]. Over the years, many interventions have been directed at the referral process.…”
Section: Introductionmentioning
confidence: 99%